Implementation of Principal’s Academic Supervision Management in Improving the Quality of Teachers’ Professional Competence - Shofiah, Nyimas; Macariola, Julie Simon (PPSDP International Journal of Education, 2025)
This study discusses the implementation of the principal’s academic supervision management in improving the quality of teacher’s professional competence at SDN 38 Palembang. The method used in this study is qualitative descriptive analysis, while data collection techniques are carried out through interviews and observations. From the results of data processing, it can be concluded that the principal’s academic supervision in improving teacher’s professionalism at SDN 38 Palembang shows that it has been implemented well in accordance with applicable provisions or has been in accordance with standards. The stages of academic supervision consist of pre-observation, observation and post-observation. The principal follows up by holding post-supervision activities, to reflect on the results of the supervision that has been carried out. Then develop data collection instruments in order to identify and analyze problems or learning development needs and carry out follow-up in the form of discussions and then listen to the explanation of the teacher concerned. This activity is intended to find out and identify various difficulties and advantages or disadvantages of teachers during the learning process at school so that student-centered learning is achieved.